Expert research in the field of environmental protection under the laws of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The article describes the types of examinations conducted in the field of environmental protection under the laws of the Republic of Kazakhstan. Depending on the task expert studies are divided into public and judicial. The differences forensic environmental impact assessments of the state environmental expertise. The shown are subject to legal and environmental assessments, the problems solved by this kind of expert research, the category of cases in which forensic appointed environmental assessments.Key words: ecology, crime, legal proceedings, evidence, experts, investigators, experts.